Clerical sexual abuse how the crisis changed US catholic church-state relations - Formicola, Jo Renee; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The book discusses the changing relationship between American Catholic Bishops and civil authorities in the United States, as civil authority has eclipsed traditional Catholic ecclesiastical privilege and clerical exemption resulting from the hierarchical mismanagement and cover-up of clerical sexual abuse in the United States.
Keywords: Social sciences; Religion and sociology; Political theory; Public policy; Human rights; Political sociology; Social Sciences; Political Sociology; Sociology of Religion; Public Policy; Social Aspects of Religion; Political Theory; Human Rights